The Legal Basis for the Ownership of the Waqf Property in the Book “Hidayah” by Marghinani - Mirzaevna, Kenjaboeva Rakhshana (International Journal of Psychosocial Rehabilitation, 2020)
In the IX-XIII centuries, Movarounnahr became one of the most important centers of development of jurisprudence, where thousands of faqihs worked. Our compatriot Burhoniddin Marghinani has a special place among Movarounnahr jurists. As a great representative of the Hanafi School, he made a great contribution to the development of jurisprudence.Burhoniddin Marghinani's work “Hidoyah” is the main textbook, manual, program in all madrassas and dorulfuns of the Muslim world. State and religious leaders, public figures, scholars and scholars used the work of Burhoniddin Marghinani and relied on him.From history to the present day, societies have established institutions to meet the needs of social assistance among themselves. The social assistance institutions established today have been implemented in Islamic society through its foundations since its earliest days. As the waqf institution expanded, special jurisprudence books were classified about it, and separate chapters were devoted to the subject of the waqf in each general jurisprudence book.In the tenth and thirteenth centuries, the science of jurisprudence was particularly advanced, during which many works on jurisprudence were written. One of such books is “Hidoyah” by Burhoniddin Marghinani. The waqf chapter of the book deals with various topics related to waqf ownership, in particular, the disposal of waqf property, waqf agreement, bequest of property waqf, and transfer of waqf property to the trustee, undivided, divisible and indivisible, waqf of shared property.